Budidaya Maggot Sebagai Solusi Pengelolaan Limbah Rumah Tangga Di Kampung Keatif Sugih Waras - Allysa Ramahdia Putri; Dilla Oktya Sari; Zakiyah Nur Azizah; Abdul Ghofururrohim; Muhammad Faiz Alghifari; Amir Hamzah (LKP KARYA PRIMA KURSUS, 2026)
This study examines the integration of household waste management and Black Soldier Fly (BSF) maggot feed production as a sustainability strategy in Kampung Kreatif Sugih Waras, Palembang. The research used a qualitative approach through observation, interviews, documentation, and literature review. The results show that the utilization of organic waste through maggot cultivation can reduce household waste volume, produce alternative feed, and generate organic fertilizer from the residue of decomposition. This program has positive impacts on environmental, economic, and social aspects, while also strengthening community participation and the development of environmentally friendly MSMEs. Thus, the integration of household waste management and maggot feed production can serve as a community-based sustainability model that is worth replicating in other areas.